2015
DOI: 10.1016/j.envres.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles affect on gene expression of inflammatory and neurodegenerative responses in mouse brain neural cells

Abstract: Silver nanoparticles (AgNPs) have antibacterial characteristics, and currently are applied in Ag-containing products. This study found neural cells can uptake 3-5 nm AgNPs, and investigated the potential effects of AgNPs on gene expression of inflammation and neurodegenerative disorder in murine brain ALT astrocytes, microglial BV-2 cells and neuron N2a cells. After AgNPs (5, 10, 12.5 μg/ml) exposure, these neural cells had obviously increased IL-1β secretion, and induced gene expression of C-X-C motif chemoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(72 citation statements)
references
References 46 publications
3
69
0
Order By: Relevance
“…Previous studies showed that AgNPs increased the permeability of brain microvessel endothelial cells through the release of proinflammatory mediators, which was responsible for AgNPs induced BBB inflammation (Trickler et al, 2010). Recent researches on inflammatory and neurodegenerative responses revealed that AgNPs could also induce IL-1b secretion and increase the gene expression of C-X-C motif chemokine 13 in murine brain ALT astrocytes (Huang et al, 2015). Accordingly, it was confirmed that AgNPs stimulation could mediate cellular biological functions through altering inflammatory factors secretion and this effect was independent of silver ions as indicated in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that AgNPs increased the permeability of brain microvessel endothelial cells through the release of proinflammatory mediators, which was responsible for AgNPs induced BBB inflammation (Trickler et al, 2010). Recent researches on inflammatory and neurodegenerative responses revealed that AgNPs could also induce IL-1b secretion and increase the gene expression of C-X-C motif chemokine 13 in murine brain ALT astrocytes (Huang et al, 2015). Accordingly, it was confirmed that AgNPs stimulation could mediate cellular biological functions through altering inflammatory factors secretion and this effect was independent of silver ions as indicated in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…AgNPs were mainly taken up by astrocytes and they strongly affected the cell morphology. Although the timeand concentration-dependent accumulation of AgNPs in astrocytes did not compromise the cellular viability or the basal metabolism in contrast to the effect induced by the identical amounts of silver as AgNO 3 (Luther et al, 2011(Luther et al, , 2012, internalization of AgNPs in astrocytes through endocytotic uptake processes induced proinflammatory cytokine secretion for inflammatory responses (Huang et al, 2015) and the strong up-regulation of metallothioneins (Luther et al, 2012). The synthesized metallothioneins in astrocytes may store nanoparticle-derived silver ions, posing the potential protective effects in the brain (Hohnholt et al, 2013).…”
mentioning
confidence: 99%
“…329 Moreover, AgNPs had been reported to be toxic to the liver, 330 skin, 331 lung, 332 and neural cells. 333 In conclusion, the AgNPs show toxic effects to all kinds of cells by interfering with their metabolic pathways, induction of apoptosis, and producing superoxides, genotoxicity, or other cytological consequences. However, there is still not enough data available to conclude what the toxic effects of AgNPs are due to the different sizes, shapes, and features of AgNPs.…”
Section: Cytotoxicity Of Agnps On Normal Cellsmentioning
confidence: 99%
“…[43][44][45] In addition, AgNPs have a broad tissue distribution in vivo, the liver is the major target organ, followed by the spleen, brain, lung, liver, kidney, and testis. [46][47][48][49][50] In this study, we first aimed to investigate whether AgNPs have an impact on LCs and SCs of testis.…”
Section: Cytotoxic Effects Of Agnps In Lcs and Scsmentioning
confidence: 99%